Experimental studies on different liquid pool fires inside the compartment. (October 2019) - Sahu, Deepak; Jain, Shorab; Gupta, Akhilesh; Kumar, Surendra
Abstract: Experimental studies have been carried out using three distinct liquid fuel fires to explore the effect of fuel on fires. The test facility consist of a compartment of dimensions 4 m × 4 m × 4 m with a door opening of size 2 m height and 1 m width. Three fuels - diesel, isopropanol and methanol, used as fire sources, are placed inside a pan of 60 cm diameter and 15 cm height. These fuels have different nature; diesel contains sooty properties while isopropanol and methanol contain the oxygenated properties. The experiments are carried for a duration of 1500 s. Thermal environment development inside the compartment is investigated using thermocouples and heat fluxes located at different locations inside the compartment. The average heat release rate are found 473, 245 and 78 kW in diesel, isopropanol and methanol fires respectively. It is observed that the fuel properties (heat of combustion, burning rate, sootiness etc.) have a most important role in the growth of compartment fire. Soot production and concentration of CO and CO2 depends on nature of fuels. Smoke extinction area is found to be higher in diesel fuel fire compared to methanol and isopropanol fuel fires.